Boron speciation and extractability in temperate and tropical soils: A multi-surface modeling approach. (December 2020) - Van Eynde, Elise; Weng, Liping; Comans, Rob N.J.
Abstract: Boron is an essential micronutrient for plants, but can also be toxic when present in excess in the soil solution. A multi-surface geochemical model was used to assess the important processes that affect the distribution of the geochemically reactive B in soils over the solution and solid phase. The multi-surface model was based on the adsorption of B on dissolved and solid humic acids, representing reactive organic matter, ferrihydrite, representing the Fe and Al (hydr)oxides, and clay mineral edges. In addition, the performance of previously proposed extraction methods for measuring reactive B was evaluated. Based on B measured in 0.01 M CaCl2 soil extracts (7–85 μmol kg −1 soil), we calculated the reactive boron concentration for 5 temperate and 5 tropical soils (8–106 μmol kg −1 soil). We found that extractions with 0.43 M HNO3 or with 0.2 M mannitol + 0.1 M triethanolamine buffer extract on average 240 and 177% of the reactive B predicted by the model, thus releasing additional B that is assumed to be not or only very slowly available for exchange with the soil solution. Reactive B calculated by the model corresponded best to the B measured in a 0.05 M KH2 PO4 (pH 4.5) extraction. In general, the multi-surface modeling showed that 68% or more of reactive boron was present in the solution phase for the soils in this study and that the adsorption was dominated by oxides in the tropical soils, while solid organic matter was the main adsorbent in the temperate soils. When changing the soil pH(CaCl2 ), B concentration was found to decrease with increasing pH, and both experimental data and modelling suggests that this effect is mainly due to increased binding of B to organic matter. Graphical abstract: Image 1 Highlights: Multi-surface modeling calculations of reactive B are in best agreement with B measured in 0.05 M KH2 PO4 extraction. Extractions with 0.43 M HNO3 or with 0.2 mannitol (pH 7.3) resulted in higher concentrations than calculated reactive B. Oxides are most important for B adsorption in acidic tropical soils, organic matter for temperate and high pH soils. In general, only a minor part of natural reactive B is retained by the solid phase in soils with pH(CaCl2 ) lower than 6.